Utilization of Bitumen Modified with Pet Bottles as an Alternative Binder for the Production of Paving Blocks - Temitope Awolusi; Daniel Oguntayo; Ahmed Farouk Deifalla; Emmanuel Babalola; Fejiro Natie; Oluwasegun Aladegboye; Marc Azab (Salehan Institute of Higher Education, 2023)
This study considers the utilization of bitumen modified with molten polyethylene terephthalate (PET) waste bottles as an alternative binder in paving blocks. PET waste was used at 2, 4, 6, 8, and 10% to modify bitumen in the production of paving blocks. Compressive strength test and skid resistance test were conducted on the paving block samples to evaluate their mechanical strength properties, while water absorption and the Cantabro abrasion tests were carried out to ascertain the durability of the paving block samples. The PET-modified bitumen paving blocks (PMBPB) have enhanced compressive strength and skid resistance compared to unmodified bitumen paving blocks. Also, a significant reduction in water absorption rate of up to 56% was achieved in PET-modified bitumen paving blocks (PMBPB) compared to the unmodified sample. The abrasion loss in the PMBCB samples was the least compared to that in normal cement paving blocks and unmodified bitumen paving blocks. The maximum compressive strength and least water absorption for the PET-modified bitumen concrete paving blocks were obtained at a 10% PET replacement level. It can be concluded that enhanced compressive strength and durability in cement paving blocks and unmodified bitumen paving blocks could be achieved with the use of PET modified bitumen in concrete paving block production, and this will also encourage PET waste recycling and contribute meaningfully to sustainability in concrete paving block production. Doi: 10.28991/CEJ-2023-09-01-08 Full Text: PDF